Studi Komparatif Analisis Isi Lambung Ikan Barau (Hampala macrolepidota Kuhl Dan Van Hasselt, 1823) di Danau Teluk Petai dan Danau Tanjung Kudu Kabupaten Kampar Provinsi Riau - Arrasyidi, Muammar Rasyid; Efawani, Efawani; Eddiwan, Eddiwan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
AbstractBarau fish (Hampala macrolepidota) is a carnivorous fish found in Tanjung Kudu Lake and Teluk Petai Lake. The quality of the waters in the two lakes is different, it is thought that it has an influence on the availability of food in the waters, and will make a difference to the stomach contents of the barau fish. To find out the stomach contents of barau fish, a study was carried out in October-December 2020. From the data analysis using the Index of Preponderance (IP), 55 fish samples from Lake Teluk Petai and 30 from Tanjung Kudu Lake, the results obtained shows that the main food of Barau fish is fish, with an IP value of 68.60% from the Teluk Petai Lake and 54.59% from the Tanjung Kudu Lake. Other types of food found in the stomach of barau fish are insects, plants and crustaceans. Of the two lakes, only insects, there were significant differences after statistical tests were carried out. The results above show that the water quality influences the availability of food for barau fish. Keywords: Petai Bay Lake, Tanjung Kudu Lake, Gastric Fill, Barau Fish